2015
DOI: 10.7745/kjssf.2015.48.6.634
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Effect of Citric Acid and Ethylenediaminetetraacetic Acid on Cadmium Extractability in Arable Soil

Abstract: Chelating agents have been proposed to improve the efficiency of phytoextraction of heavy metal hyperaccumulator. However, little studies to elucidate mechanism of chelating agents to increase cadmium (Cd) extractability have been conducted. The objectives of this study were to evaluate effect of different chelating agents on Cd extractability and to determine mechanism of Cd mobilization affected by these agents. An arable soil was spiked with inorganic Cd (CdCl 2 ) to give a total Cd concentration of 20 mg C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Therefore, the application of chelating agents to conventional phytoremediation techniques in Cd contaminated soil has received keen interest. Although these techniques are highly effective, we observed Cd immobilization with CA in our recent pilot study [20]. We reported that concentrations of non-bioavailable Cd fractions increased following addition of CA, but we did not precisely demonstrate the related mechanism of Cd immobilization with CA.…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…Therefore, the application of chelating agents to conventional phytoremediation techniques in Cd contaminated soil has received keen interest. Although these techniques are highly effective, we observed Cd immobilization with CA in our recent pilot study [20]. We reported that concentrations of non-bioavailable Cd fractions increased following addition of CA, but we did not precisely demonstrate the related mechanism of Cd immobilization with CA.…”
Section: Introductionmentioning
confidence: 61%
“…To identify the availability of heavy metals in contaminated soils, we performed a sequential extraction method for heavy metals as described in previous studies [20,29,32,33]. Among the present fractions, F1 contained the most bioavailable Cd.…”
Section: Resultsmentioning
confidence: 99%